2012
DOI: 10.1007/s12185-012-1004-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased fibrinolysis increases bleeding in orthopedic patients receiving prophylactic fondaparinux

Abstract: We evaluated hemostatic markers in patients who underwent major orthopedic surgery, including total hip and total knee arthroplasty, and were treated for the prophylaxis of deep vein thrombosis (DVT) with or without fondaparinux (anti-Xa group, n = 98 and without anti-Xa group, n = 20). The frequency of DVT was significantly higher in the without anti-Xa group than in the anti-Xa group, but the reduction of hemoglobin and fibrinolytic marker levels was significantly lower in the without anti-Xa group than in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
0
26
2
Order By: Relevance
“…2,4,5 Increased fibrinolytic activity in TKA and THA patients has also been associated with increased bleeding amount. 6,7 One of the main components of the fibrinolytic system is plasminogen activator inhibitor 1 (PAI-1), which is synthesized from endothelium, liver, and adipose tissue. 8 The PAI-1 inhibits tissue plasminogen activator (tPA), thereby inhibiting its activator effect on inactive plasminogen to active plasmin, which degrades fibrin.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,5 Increased fibrinolytic activity in TKA and THA patients has also been associated with increased bleeding amount. 6,7 One of the main components of the fibrinolytic system is plasminogen activator inhibitor 1 (PAI-1), which is synthesized from endothelium, liver, and adipose tissue. 8 The PAI-1 inhibits tissue plasminogen activator (tPA), thereby inhibiting its activator effect on inactive plasminogen to active plasmin, which degrades fibrin.…”
Section: Introductionmentioning
confidence: 99%
“…These patients received 30 mg of edoxaban by oral administration once a day for 14 days beginning 24 hours after the discontinuation of lumbar anesthesia. Of these 99 patients, 12 exhibited DVT, and 25 had MB, defined as a reduction in the hemoglobin level by > 2 g/dL compared with that at Day 1 or a hemoglobin level < 7 g/dL (Table ). The APTT assay was performed in plasma from 30 healthy volunteers (HVs; 10 females and 20 males; age, 21 years; 20‐24 years) and 22 patients treated with warfarin (16 females and 6 males; 63.0 years; 54.5‐71.3 years) and compared with the findings in plasma from patients treated with edoxaban.…”
Section: Resultsmentioning
confidence: 99%
“…Massive bleeding (MB) due to withdrawal of anticoagulants is sometimes observed in these patients, although these drugs are generally considered to induce little bleeding. While the above drugs are usually difficult to monitor by routine coagulation tests, anti‐Xa assays have recently been developed to monitor LMWH and oral anti‐Xa inhibitors . However, the anti‐Xa assay is not a routine assay and is more expensive than assays for activated partial thromboplastin time (APTT) or prothrombin time (PT).…”
Section: Introductionmentioning
confidence: 99%
“…The above results confirmed that both assays were capable of reproducibly measuring the anti-Xa activity within a clinically relevant range. 16,17 As for the intra-individual variability, patients who underwent lower intestinal surgery and received 2.5 mg of FPX daily demonstrated a gradual but significant increase in anti-Xa activity. In terms of inter-individual variability, the plasma levels of anti-Xa activity showed a significant negative correlation with body weight and with BMI.…”
Section: Discussionmentioning
confidence: 99%